2012
DOI: 10.1017/s0029665112001966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of folic acid supplementation during pregnancy on growth and cognitive development of the offspring: a pilot follow-up investigation of children of FASSTT study participants

Abstract: It is well established that folic acid supplementation in the early stages of pregnancy can reduce the risk of neural tube defects and some other congenital malformations (1) . Observational research also suggests that maternal folate intake may have a long-term effect on the neurocognitive development of the offspring (2)(3) , however, the evidence so far is inconclusive. The current study aimed to investigate the effect of folic acid supplementation during pregnancy on growth and cognitive development of you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A pilot study ( n 39), conducted by our group, examined the effect of folic acid supplementation in the second and third trimester of pregnancy and subsequent cognitive performance of the child. The novel results showed that children (aged 3 years) born to mothers supplemented with folic acid, scored significantly higher in the cognitive domain of the Bayley's development assessment ( 22 ) . These highly promising results from this RCT now need to be confirmed on a larger scale.…”
Section: C1 Metabolism B-vitamins and Early Brain Healthmentioning
confidence: 94%
“…A pilot study ( n 39), conducted by our group, examined the effect of folic acid supplementation in the second and third trimester of pregnancy and subsequent cognitive performance of the child. The novel results showed that children (aged 3 years) born to mothers supplemented with folic acid, scored significantly higher in the cognitive domain of the Bayley's development assessment ( 22 ) . These highly promising results from this RCT now need to be confirmed on a larger scale.…”
Section: C1 Metabolism B-vitamins and Early Brain Healthmentioning
confidence: 94%
“…The only RCT to date to look at the specific effect of 0•4 mg/d FA in isolation was conducted at this centre, namely the FASSTT trial (ISRCTN19917787) (13) and provided a unique opportunity to specifically investigate the effect of FA supplementation in the second and third trimesters on subsequent cognitive performance of the child. The results showed that children of mothers supplemented with FA throughout pregnancy performed better in the cognitive domain at age 3 years (72) and the verbal domain at 7 years (73) . These findings are in agreement with the results of animal studies, whereby continuation of maternal FA supplementation increased serum folate concentrations in pregnant rat dams and improved neurodevelopment in their pups, from newborns to adulthood (74) .…”
Section: Maternal Folate and Offspring Cognitive Performancementioning
confidence: 96%
“…The only RCT to date to look at the specific effect of 0·4 mg/d FA in isolation was conducted at this centre, namely the FASSTT trial (ISRCTN19917787) ( 13 ) and provided a unique opportunity to specifically investigate the effect of FA supplementation in the second and third trimesters on subsequent cognitive performance of the child. The results showed that children of mothers supplemented with FA throughout pregnancy performed better in the cognitive domain at age 3 years ( 72 ) and the verbal domain at 7 years ( 73 ) .…”
Section: Maternal Folate and Offspring Cognitive Performancementioning
confidence: 99%
“…However, an intervention study from this centre, the Folic Acid Supplementation in the Second and Third Trimesters trial (9) , provided a unique opportunity to follow-up the children of trial participants and found direct evidence of beneficial effects of folic acid provided to mothers during pregnancy on the cognitive performance of their children at age 3 and 6 years (i.e. as measured by validated tools, the Bayley Scales of Infant and Toddler Development and Weschler Preschool and Primary Scale of Intelligence, respectively) (24,25) . Thus maintaining optimal maternal folate throughout pregnancy, well beyond the early period known to be protective against NTD, may be beneficial for brain development and functioning in the child.…”
Section: Health Impacts Of Folate and Related B Vitamins Through The mentioning
confidence: 99%